Australia's Changing Religious Profile—Rising Nones and Pentecostals, Declining British Protestants in Superdiversity: Views from the 2016 Census. (25th October 2017) - Bouma, Gary; Halafoff, Anna
Abstract : The 2016 Australian Census reveals continued change in Australia's religious diversity. While reviewing some of the highlights of this development–the continuing increase in the 'no religion' category, the first ever decline in Catholic numbers, and the rise of Hindus and Sikhs–several religious groups, which are not usually combined in the census, actually when grouped together represent most of the Pentecostal and charismatic churches and form the fourth largest religious group in Australia. These changes are set in a comparative context, internationally and intergenerationally. The religious diversity and Anglican retention rates of Stonnington–one of Melbourne's 21 Cities–are examined as a window on local diversity and change. Finally, we discuss three main categories of religion in contemporary Australia: the 'nones'; the spiritual but not religious; and the religious and spiritual. The data reveal a new context of superdiversity in Australia.